2020
DOI: 10.1146/annurev-animal-021419-083626
|View full text |Cite
|
Sign up to set email alerts
|

Omics Technologies for Profiling Toxin Diversity and Evolution in Snake Venom: Impacts on the Discovery of Therapeutic and Diagnostic Agents

Abstract: Snake venoms are primarily composed of proteins and peptides, and these toxins have developed high selectivity to their biological targets. This makes venoms interesting for exploration into protein evolution and structure–function relationships. A single venom protein superfamily can exhibit a variety of pharmacological effects; these variations in activity originate from differences in functional sites, domains, posttranslational modifications, and the formations of toxin complexes. In this review, we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 210 publications
0
15
0
Order By: Relevance
“…The investigation of venom diversity is strongly multidisciplinary, in which omics technologies, including genomics, transcriptomics, and proteomics, play an increasingly large role in the field of venom research [ 43 , 44 ]. Nowadays, the bottom-up (BU) and the top-down (TD) approach have become the gold standard in snake venom proteomics and the advantages and disadvantages of both have been extensively discussed [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of venom diversity is strongly multidisciplinary, in which omics technologies, including genomics, transcriptomics, and proteomics, play an increasingly large role in the field of venom research [ 43 , 44 ]. Nowadays, the bottom-up (BU) and the top-down (TD) approach have become the gold standard in snake venom proteomics and the advantages and disadvantages of both have been extensively discussed [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms via which these organisms deliver toxic components are related to how toxins have evolved and exerted their ecological functions [2]. As a result of millions of years of evolution, the diversity of molecular structures and activities is immeasurable, with hidden functions and structures only recently disclosed by modern omics techniques associated with classical pharmacological studies [3]. Thus, the holistic molecular genetic analyses of venomous animals utilizing, for example, transcriptome in combination with proteome studies of venom glands, have revealed not only the diversity of a set of substances produced by a given organism that inhabits a particular biome but also the uniqueness of such molecular repertoire expressed as active components of biological materials, such as venoms [4][5][6][7][8].…”
mentioning
confidence: 99%
“…However, the newer technologies such as venomics, proteomics, transcriptomics, metabolomics and genomics are progressing rapidly for characterization of overall snake venom composition. 33 This should provide further diversification and understanding of snake venom compositions and its biological active proteins for the treatment of heart disease, inflammation, cancer therapy or as a new tool for clinical diagnostic parameters.…”
Section: Snake Venomics and Proteomicsmentioning
confidence: 99%